“Turn that frown upside-down”: A contextual account of emoticon usage on different virtual platforms - Kaye, Linda K.; Wall, Helen J.; Malone, Stephanie A. (Computers in human behavior, 2016)
Evidence highlights the prevalent usage of emoticons within digital forms of textual communication and the impact on the recipient. However, little evidence demonstrates the interpersonal functions for the user and whether this varies as a product of virtual platform. This formed the basis for the current study in which participants (N = 92) provided open-ended accounts of their reasons for using emoticons across three virtual platforms (email, text message, and social networking site), and their general emoticon usage across these. Responses revealed a number of themes on reasons for emoticon usage. The first was; “aiding personal expression”, with sub-themes of; “establishing emotional tone”; and “to lighten the mood”. Other themes were “reducing ambiguity of discourse” and “appropriateness of context”. Overall, there was consistency across platforms, on both the personal and interpersonal functions which emoticons served. However, some disparity was identified as email platforms were deemed inappropriate for emoticon use, regardless of the fact that emoticons were recognised as important emotional aids for communication. Taken together these findings highlight the importance of emoticon usage for the user, through a contextual lens to recognise the influential factors upon these behaviours and the implications this has for digital text-based communication. In this regard, this contributes further conceptualisation of one aspect of hyperpersonal communication within virtual interactions, and how different platforms may permit these self-presentational efforts to a greater or lesser extent. •Qualitative approach to understanding usage behaviour for emoticons.•Contextual account of emoticon usage across digital platforms.•Benefit to both user and recipient in their use of emoticons.